Personalized Dendritic Cell Vaccines—Recent Breakthroughs and Encouraging Clinical Results - Mastelic-Gavillet, Beatris; Balint, Klara; Boudousquie, Caroline; Gannon, Philippe O.; Kandalaft, Lana E. (Frontiers in Immunology, 2019)
With the advent of combined immunotherapies, personalized dendritic cell (DC)-based vaccination could integrate the current standard of care for the treatment of a wide rangelarge variety of tumors types. Due to their proficiency at antigen presentation, dendritic cellsDC are key coordinators of the innate and adaptive immune systemity, and play have a crucial partcritical roles in the induction of antitumor immunity. However, despite proven immunogenicity and their favorable safety profiles, even in patients with advanced disease, DC-based immunotherapies have been disappointingnot succeeded in terms ofat inducing significant objective clinical responses. Emerging data suggest that the combination of DC-based vaccination with other cancer therapies may fully unleash the potential of DC-based cancer vaccines and improve patient survival. In this review, we discuss the recent efforts to develop innovative personalized DC-based vaccines and their use in combined therapies, with a particular focus on ovarian cancer and the promising results of mutanome-based personalized immunotherapies.